Wildlife diversity and community structure in northern deciduous forest of Bangladesh - Jaman, Mohammad Firoj; Rabbe, Md Fazle; Saha, Arnob; Shome, Ashikur Rahman; Alam, Md Mahabub (Journal of Bangladesh Academy of Sciences, 2023)
Monitoring wildlife communities in protected areas is pivotal to successful conservation efforts. This study employed a direct observations-based approach to examine the diversity and community structure of wildlife in four protected deciduous national parks (Ramsagar, Birganj, Singra, and Nawabganj) in the northern Dinajpur district of Bangladesh. This study assessed the wildlife assemblage structures by measuring α diversity and β diversity. This research recorded a total of 159 wildlife species under 29 orders. Singra National Park displayed the highest species richness (N=73) and was found to be more diverse (H=3.36 ± 0.16) and even in distribution (J=0.9 ± 0.01). Analysis of Similarity test showed significant differences across all study sites (R=0.5216; p=0.0001). Whittaker Plot ranked Dendrocygna javanica as dominating, species making the community uneven. We found significant differences in species richness among seasons (F2, 9=17.8, p=0.0001). For example, winter and rainy seasons were significantly richer over summer. This study identified profound human intrusions, which could potentially impact wildlife communities in the study area. Our findings underscore the conservation efforts to safeguard the threatened species in the study area. J. Bangladesh Acad. Sci. 47(2); 249-265: December 2023